Drømmen om Skolen i Soer - Albeck, Gustav (Grundtvig-studier, 1983)
The Dream of the School at Soer By Gustav Albeck Grundtvig never saw the fulfilment of his dream of a large folk high school at Sorø (Soer). He realised this when in 1848 the newly-established Danish rigsdag rejected the plan that King Christian VIII had approved shortly before his death earlier that year. Grundtvig found consolation in the thought of the many folk high schools that were shooting up in the last two decades of his life. He thus moved away from his original plan for a university open to every citizen, a centre for Denmark’s history such as, according to Grundtvig, Bishop Absalon had imagined when he established the monastery at Sorø which later became a gentlemen’s academy, supported by donations from Ludvig Holberg.Grundtvig’s first draft for the re-establishment of Sorø Academy dates from 1827, after he had read in the Edinburgh Review of the plans for the University of London. Unfortunately we possess only fragments of his manuscripts on this. When he visited Oxford and Cambridge in 1829-31 he saw how different the English university world was from the Danish, which to some degree was influenced by the German. He wished for an interaction between academic and popular education. And his success with the lectures on contemporary history which he gave in 1838 encouraged him to take part in the establishment of ‘ Danish Society’, a humanist counterpart to the Society for the Propagation of Physics, founded by H. C. .rsted.In 1866 Rosenørn-Teilmann, the minister of education, attempted to set up a commission to realise Grundtvig’s ideas from 1838 but met strong opposition from J. N. Madvig, who in particular criticized Rasmus Nielsen, a professor of philosophy, whose writings from around 1867 reveal how he imagined Grundtvig’s ideas for an interaction between academic and popular education could be put into practice. In 1872 Rasmus Nielsen proposed a plan for popular university courses which was realized 20 years later in Sweden and Finland, possibly under inspiration from English universities.In 1878-79 another minister of education, C. J. Fischer, proposed a bill* for the establishment of a state high school in or near Copenhagen. But Grundtvig’s harsh words about the university and the ‘black school’ frightened his heirs away from a conciliatory relationship between the university and a state high school for popular enlightenment. Even though the bill followed closely the ideas that Grundtvig had advocated it was nevertheless defeated, but it did gain support to the tune of 5,000 kroner for Askov’s enlarged folk high school.In the following year other spokesmen supported the idea, including Geert Winther, a doctor of philosophy who in the years 1880-1900 attempted to set up a committee of university professors to realize the plan. He received support in particular from Fredrik Nielsen, a professor of theology, who later became Bishop of Aarhus, and who in 1906 spoke out directly on plans for ‘an academy outside the university but which alongside it could offer a general education and in some ways be an introduction of Grundtvig’s ideas for the high school at Sorø’. Fredrik Nielsen did not, however, expect the plan to be realized in Sorø, but in Aarhus, and over the next few years efforts were concentrated on the establishment of ‘a Danish high school for scholarship’ in Aarhus. This received support from amongst others Harald Høffding in 1920, but was not completed until 1928.But what was the attitude of the folk high school supporters in this matter? Only a few were enthusiastic. From 1909 Valdemar Brücker fought to realize the Sorø plan as the school for a general education of the people which could win equality with the academic one. The proposal reached parliament (rigsdagen) but was defeated.Within the folk high school Brücker was supported by Tormod Jørgensen, Jacob Lange and Anders Vedel. But writing in højskolebladet (High School Periodical) in 1930 Holger Begtrup characterizes Grundtvig’s high school writings as ‘old papers presenting a plan that fortunately was never realized’.However, Krogerup High School, established by Professor Hal Koch after the Second World War, was an initiative that tended towards an institution akin to Sorø, though it never turned into a realisation of Grundtvig’s great visions.